If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 1 + s Solving 13 = 1 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. 13 + -1s = 1 + s + -1s Combine like terms: s + -1s = 0 13 + -1s = 1 + 0 13 + -1s = 1 Add '-13' to each side of the equation. 13 + -13 + -1s = 1 + -13 Combine like terms: 13 + -13 = 0 0 + -1s = 1 + -13 -1s = 1 + -13 Combine like terms: 1 + -13 = -12 -1s = -12 Divide each side by '-1'. s = 12 Simplifying s = 12
| 4x^2-16x+16=36 | | 5.59x=27.95 | | (7+2x)5=11+6x | | 5/8j=15/24 | | 21=6-x+4x | | -9+u=-2 | | 2x+95=6x+54 | | 2x^2-7x-4=36 | | x+x=138 | | 49x^2+34x+36=0 | | 17+3(w-2)-11w=-7(w+2) | | x+x=329 | | 4+2s-3=7s+19-3s | | 5x+66=10x-9 | | 3x-27=2y | | 50x=60(x+20) | | 8k-10=3(6-2k) | | 7x+19-5x-2= | | 49(x-2)=2(x+3) | | 3(7b-9)=21 | | x+x=284 | | f(t)=7t+3 | | 8-5+3c=25 | | x-0.30x=245 | | 8x^2-104x+240=0 | | 10+4(2a+2b)= | | 3x+18=2(x-18) | | 8+5+3c=25 | | 9x^9/36x^5y | | Ln(x^2-16)=1 | | 5x+11-(2x-3)= | | 4x+8x+25+3x-15=160 |